Does Afta And China's Entry Into Wto Affect Fdi In Asean Countries? - Abd Karim , Mohd Zaini; Othman, Yusairi (Asian Academy of Management (AAM), 2005)
Foreign direct investment (FDI) plays an important role in the rapid economic development of the newly industrializing and developing economies of Southeast Asia. In terms of the regions attractiveness, ASEAN region is a leading recipient of FDI flows in the developing world, with five ASEAN countries in the top 20 developing-countries recipients of long-term global capital flows from 1997 to 1998. While the creation of AFTA may help FDI inflows to ASEAN countries, China's entry into World Trade Organization (WTO) will be the opposite and has caused a great deal of worry to ASEAN countries. The objective of this paper is to empirically determine the effect of ASEAN Free Trade Area (AFTA) and China's entry into WTO on the inflows of FDI into ASEAN countries. To achieve the objectives, Seemingly Unrelated Regression (SUR) method was used to estimate the FDI equation. In general, the results indicate that the establishment of AFTA had a positive effect on FDI inflows to ASEAN countries while China's entry into WTO is the opposite.